2009
DOI: 10.1002/jnr.22088
|View full text |Cite
|
Sign up to set email alerts
|

Desacyl‐ghrelin and synthetic GH‐secretagogues modulate the production of inflammatory cytokines in mouse microglia cells stimulated by β‐amyloid fibrils

Abstract: Data from Alzheimer's disease (AD) patients and AD animal models demonstrate the accumulation of inflammatory microglia at sites of insoluble fibrillar beta-amyloid protein (fAbeta) deposition. It is known that fAbeta binds to CD36, a type B scavenger receptor also involved in internalization of oxidized low-density lipoprotein (LDL), and initiate a signaling cascade that regulates microglial recruitment, activation, and secretion of inflammatory mediators leading to neuronal dysfunction and death. The recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 46 publications
4
64
0
Order By: Relevance
“…7A), consistent with previous reports that desacyl ghrelin does not activate the ghrelin receptor (Bednarek et al 2000, Johansson et al 2008. In contrast, desacyl ghrelin has been reported to have synergistic or antagonistic effects on ghrelin-dependent physiological events (Filigheddu et al 2007, Bulgarelli et al 2009). Desacyl ghrelin fragments protect pancreatic b-cells from oxidative stress to prevent diabetes in streptozotocin-treated rats (Granata et al 2012).…”
Section: Figuresupporting
confidence: 90%
See 1 more Smart Citation
“…7A), consistent with previous reports that desacyl ghrelin does not activate the ghrelin receptor (Bednarek et al 2000, Johansson et al 2008. In contrast, desacyl ghrelin has been reported to have synergistic or antagonistic effects on ghrelin-dependent physiological events (Filigheddu et al 2007, Bulgarelli et al 2009). Desacyl ghrelin fragments protect pancreatic b-cells from oxidative stress to prevent diabetes in streptozotocin-treated rats (Granata et al 2012).…”
Section: Figuresupporting
confidence: 90%
“…6D) and found that digested forms of ghrelin exert cellular functions in a ghrelin-receptor-dependent fashion. Importantly, these results indicate that ghrelin might have diverse health-related effects under the influence of thrombotic/thrombolytic system, including antiinflammatory (Li et al 2004, Chorny et al 2008, Waseem et al 2008, Bulgarelli et al 2009) and cardiovascular effects (Baldanzi et al 2002, Rossi et al 2007, in addition to its previously reported roles in GH release and appetite control (Wren et al 2001, Asakawa et al 2005, Drucker 2007, Sun et al 2008. Synthetic human o-ghrelin(15) can also be cleaved into smaller peptide fragments, such as o-ghrelin (14) or o-ghrelin(13) (Fig.…”
Section: Figurementioning
confidence: 71%
“…Of note, the actions of ghrelin in neuroprotection seem to be specifically mediated by the inhibition of proapoptotic molecules associated with mitochondrial pathways and by activating endogenous protective molecules (Miao et al 2007). Interestingly, ghrelin acts by inhibiting apoptotic pathways regardless of its acylation (Chung et al 2008); however, while AG acts through GHSR1a, UAG would bind to the CD36 scavenger receptor to exert these actions (Bulgarelli et al 2009). …”
Section: Nonendocrine Actionsmentioning
confidence: 99%
“…Both ghrelin and DAG share an identical amino acid sequence, with the only difference that DAG lacks an O-n-octanoylation at serine 3 (Chen et al, 2009). This was believed to render DAG unable to bind with the growth hormone secretagogue receptor (now preferably denoted as ghrelin receptor (IUPHAR/BPS, 2015), and numerous studies have been performed to try to elucidate the receptor on which DAG exerts its function (Bulgarelli et al, 2009;Delhanty et al, 2012Delhanty et al, , 2013Pei et al, 2014).…”
Section: Introductionmentioning
confidence: 98%